Salient features of sticker tumour in dogs and its diagnosis by cytopathology and histopathology technique - MUGALE, MADHAV; SINGH, VIKASH; GAVHANE, DNYANESHWAR; GOSWAMI, GAGAN (The Indian Journal of Animal Sciences, 2014)
Six dogs of various ages, breeds and sex showed tumourous growth confined to extragenital regions. The study was aimed at diagnosing tumourous growth using routine technique clinically and pathologically. Cytological techniques and later the results were compared with routine histopathology. Two male Labrador dogs, 1 female Spitz and 3 male non-descript dogs with tumour masses over and around the genital organ were used. Tumour impression sample and excised tumour were used as material for the study. Fine needle aspiration cytopathology (FNAC) with various cytological stains and routine histopathology with haematoxylin and eosin staining were performed. Grossly, the tumour masses appeared as single or multiple irregular, cauliflower like and had a tendency to bleed and in almost all cases colour was pink to red. Cytologically, the tumour yielded a homogenous, sheet-like high cellular mass. Cytoplasm with punctate vacuoles, anisokaryosis with anisonucleoliosis and coarse to reticulate nuclear chromatin were prominent features. Histopathology showed sheets of round cells with nuclear and cytoplasmic variations. The study concluded that cytopathology could be used as a quick, rapid, field diagnostic technique in combination with histopathology for the diagnosis of TVTs.